Evaluation of the Quality Assurance Practices of the College of Education Programs of a Philippine Local University - Prado, Ramona (Journal of Interdisciplinary Perspectives, 2025)
This study investigates the quality assurance practices in teacher education programs at a Philippine locally funded university, focusing on strategies to improve program delivery and align curricular offerings with national and global benchmarks. Despite ongoing efforts guided by accreditation standards, gaps persist in ensuring comprehensive quality assurance. Using a descriptive-evaluative method, data were gathered from institutional records, assessments, and observations involving students, faculty, and administrators in the Bachelor of Secondary Education and Bachelor of Elementary Education programs. Findings revealed that the College of Education has satisfactorily complied with standards in curriculum and instruction, faculty qualifications, institutional vision and mission, program objectives, student development services, and graduate employability and entrepreneurship. However, several areas were identified as barriers to full quality assurance, particularly student support services, funding, research productivity, instructional facilities, and community engagement. These challenges highlight the need for strategic and targeted interventions to strengthen program effectiveness. To achieve full quality assurance, long-term development planning and curricular alignment with national and international standards are essential, supported by strategic resource allocation and enhanced student services. Addressing these gaps through systematic planning and continuous improvement will ensure sustainable academic excellence and institutional effectiveness. Strengthened collaboration with accrediting bodies will also support compliance with evolving standards. Overall, the study underscores the importance of periodic evaluation, responsive policy reform, and sustained investment in teacher education to produce competent graduates who can meet the dynamic demands of the education sector.